Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1021/acsanm.2c02213
|View full text |Cite
|
Sign up to set email alerts
|

NaBH4-Assisted Synthesis of B–(Ni–Co)/MgAl2O4 Nanostructures for the Catalytic Dry Reforming of Methane

Abstract: Carbon deposition on a catalyst surface is detrimental to the dry reforming of methane (DRM) reaction. The addition of boron (B) is found to be effective in lowering carbon deposition. In this study, bimetallic Ni, Co catalysts over MgAl 2 O 4 (MA) [B−(Ni−Co)/ MA] with different Ni/Co ratios are synthesized by the NaBH 4 reduction method and examined for DRM at 600 °C and atmospheric pressure. The NaBH 4 plays crucial roles in reducing metal salt to metal, incorporating B, and enhancing the dispersion of activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 55 publications
1
8
0
Order By: Relevance
“…The carbon is deposited over the active sites of nickel, which blocks the catalyst bed, hence increasing the pressure drop along the catalyst bed, clogging the reactor, and shutting down the plant 10,11 . Consequently, preventing carbon deposition and prolonging the catalyst life are essential 12 . It is well known that particle size, surface area, surface acidity and basicity, metal dispersion, and thermal stability of the support and its interaction with metal impact global catalyst efficiency 5 .…”
Section: Introductionmentioning
confidence: 99%
“…The carbon is deposited over the active sites of nickel, which blocks the catalyst bed, hence increasing the pressure drop along the catalyst bed, clogging the reactor, and shutting down the plant 10,11 . Consequently, preventing carbon deposition and prolonging the catalyst life are essential 12 . It is well known that particle size, surface area, surface acidity and basicity, metal dispersion, and thermal stability of the support and its interaction with metal impact global catalyst efficiency 5 .…”
Section: Introductionmentioning
confidence: 99%
“…After the test, the Re-LCMNCu catalyst was examined by Raman spectroscopy, TG-DSC, and SEM, in order to understand their performance. In Raman spectral analysis (Figure a), no signal of carbon fiber was detected at 1350 cm –1 (peak D) and 1580 cm –1 (peak G), which were related to typical carbon species Figure b shows the profiles of TG-DSC analysis for Re-LCMNCu after the reforming test.…”
Section: Resultsmentioning
confidence: 99%
“…In Raman spectral analysis (Figure 11a), no signal of carbon fiber was detected at 1350 cm −1 (peak D) and 1580 cm −1 (peak G), which were related to typical carbon species. 51 Figure 11b shows the profiles of TG-DSC analysis for Re-LCMNCu after the reforming test. It was reported that the weight loss and heat release in the temperature range between 500 and 700 °C were caused by the oxidation of the deposited graphitic carbon.…”
Section: Phase and Micromorphology Characterizationmentioning
confidence: 99%
“…Except for Si and C, the introduction of boron (B) was also found to efficiently reduce the coke formation and improve the catalytic activity of the catalyst at low temperatures. [ 140 ] Shakir et al synthesized a B–NiCo/MgAl 2 O 4 catalyst by using NaBH 4 as a reducing agent, which not only reduces the Ni and Co but also introduces the B as a promoter. [ 140 ] In summary, the introduction of nonmetal promoters (especially C and B) into DRM catalysts was simple but effective.…”
Section: Effects Of Promoters On the Catalystmentioning
confidence: 99%
“…[ 140 ] Shakir et al synthesized a B–NiCo/MgAl 2 O 4 catalyst by using NaBH 4 as a reducing agent, which not only reduces the Ni and Co but also introduces the B as a promoter. [ 140 ] In summary, the introduction of nonmetal promoters (especially C and B) into DRM catalysts was simple but effective. With efficient improvement in catalytic reactivity, the introduction of nonmetal promoters into catalysts will attract more research interests to develop more efficient catalysts and deeply understand the impacts of these promoters in low‐temperature DRM reactions.…”
Section: Effects Of Promoters On the Catalystmentioning
confidence: 99%